Maternal Coping Strategies for Premature Infant: A Systematic Review - Kapti, Rinik Eko; Arief, Yuni Sufyanti; Triharini, Mira; Saidah, Qori'ila; Azizah, Nurona; Supriati, Lilik (UI Scholars Hub, 2022)
A mother’s stress due to the birth of her premature baby results in obstacles to the mother’s role, hence it requires appropriate coping strategies. This review aimed to identify coping factors, explore coping strategies by mothers with premature babies, and identify interventions for enhancing maternal coping strategies. The article navigation utilized Boolean Operator of